Performance Management of Community Counselors (Case Study: Balai Pemasyarakatan Jakarta Timur-Utara) - Taletting Langi, Andi; Luddin, Muchlis R.; Akbar, Maruf (Opción, 2019)
This study aims to in-depthly find out and analyze the application of perfor- mance management for Community Counselors at Balai Pemasyarakatan Jakarta Timur-Utara, DKI Jakarta. This study employs a qualitative approach based on a case study. The primary data in this study were obtained through in-depth inter- views with a number of stakeholder actors involved and also supported by on-field direct and participant observation techniques. Meanwhile, secondary data in this study was obtained through literature studies of relevant documents. This study found that the implementation of performance management for Community Coun- selors at Balai Pemasyarakatan Jakarta Timur-Utara is still not optimal, where the authors identified a number of major constraints that at the very least relate to aspects of the availability of human resources and its capacity, organizational gov- ernance issues, budget issues and support for facilities and other things. This study limits the scope of studies on the implementation of performance management for Community Counselors at Balai Pemasyarakatan Jakarta Timur-Utara in the aspects of planning, implementing, monitoring, evaluating and improving their performance. Through this study, the authors aim to contribute to the efforts of improving the Child Criminal Justice System in Indonesia which is focused on improving aspects of the performance management of Community Counselors at Balai Pemasyarakatan. A number of recommendations related to these improve- ment efforts are also outlined in this paper.